Korelasi antara Jumlah UMKM, Jumlah Penduduk, Tenaga Kerja dengan Pertumbuhan Ekonomi Kota Palu Tahun 2019-2023 - Ni Kadek Muliyani; Rita Suirlan; Muhtar Lutfi; Nurnaningsih Nurnaningsih; Mukhtar Tallesang (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
Economic growth measures the progress of a region. In Palu City, economic development is influenced by various factors, including total of MSMEs, population, and workforce. MSMEs play a role as driver of the local economy, while the total of population and workforce reflects the potential of human resources that can contribute to economic growth. The purpose this study is analyze the relationship between the total of MSMEs, population and workforce with economic growth in Palu City in 2019-2023. The research method uses quantitative approach with correlational associative research type. The analysis method uses Pearson Correlation. The results of the analysis show that the total of MSMEs has positive but insignificant correlation with economic growth, with low level of closeness, the total of population has positive but insignificant correlation with economic growth, with moderate level of closeness and the workforce has a positive but insignificant correlation, with moderate level of closeness with economic growth.